Evolution in Investment Treaty Law and Arbitration - Brown, Chester; Miles, Kate (Cambridge : Cambridge University Press, 2011)
International investment law is in a state of evolution. With the advent of investor-State arbitration in the latter part of the twentieth century - and its exponential growth over the last decade - new levels of complexity, uncertainty and substantive expansion are emerging. States continue to enter into investment treaties and the number of investor-State arbitration claims continues to rise. At the same time, the various participants in investment treaty arbitration are faced with increasingly difficult issues concerning the fundamental character of the investment treaty regime, the role of the actors in international investment law, the new significance of procedure in the settlement of disputes and the emergence of cross-cutting issues. Bringing together established scholars and practitioners, as well as members of a new generation of international investment lawyers, this volume examines these developments and provides a balanced assessment of the challenges being faced in the field.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: International commercial arbitration; Commercial treaties